2020
DOI: 10.1080/20013078.2020.1774144
|View full text |Cite
|
Sign up to set email alerts
|

Neuroblastoma‐secreted exosomes carrying miR‐375 promote osteogenic differentiation of bone‐marrow mesenchymal stromal cells

Abstract: Bone marrow (BM) is the major target organ for neuroblastoma (NB) metastasis and its involvement is associated with poor outcome. Yet, the mechanism by which NB cells invade BM is largely unknown. Tumour microenvironment represents a key element in tumour progression and mesenchymal stromal cells (MSCs) have been recognized as a fundamental part of the associated tumour stroma. Here, we show that BM-MSCs isolated from NB patients with BM involvement exhibit a greater osteogenic potential than MSCs from non-inf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
34
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(35 citation statements)
references
References 47 publications
1
34
0
Order By: Relevance
“…Collectively, these data suggest that NB-derived EV (and purified exosomes) are capable of triggering a pro-tumorigenic phenotype in MSC, thus contributing to tumor spread [50]. The role of NB-derived EV in promoting tumor invasiveness and metastasis was also investigated by Colletti et al [51]. They demonstrated that MSC isolated from the BM of NB patients with metastatic infiltration have a greater osteogenic potential than those isolated from patients without BM infiltration or healthy controls.…”
Section: Delivery Of Nb-derived Ev To Mesenchymal Stem Cellsmentioning
confidence: 90%
See 1 more Smart Citation
“…Collectively, these data suggest that NB-derived EV (and purified exosomes) are capable of triggering a pro-tumorigenic phenotype in MSC, thus contributing to tumor spread [50]. The role of NB-derived EV in promoting tumor invasiveness and metastasis was also investigated by Colletti et al [51]. They demonstrated that MSC isolated from the BM of NB patients with metastatic infiltration have a greater osteogenic potential than those isolated from patients without BM infiltration or healthy controls.…”
Section: Delivery Of Nb-derived Ev To Mesenchymal Stem Cellsmentioning
confidence: 90%
“…In addition, a couple of studies demonstrated that EV released by cells of the immune system are captured by NB cells, thus blocking or increasing tumor cell growth. Among all molecules contained in EV, miRNA are the most involved in modulating cell functions [48,[51][52][53]. Gene transfer through EV release [54] and shedding of immunosuppressive molecules [55] were also described in NB.…”
Section: Release Of Ev: a Form Of Bi-directional Cross-talk Between Nmentioning
confidence: 99%
“…In target cells, molecules carried by exosomes can trigger and influence several processes both in physiological and pathological conditions. In recent years, numerous evidence highlights the involvement of exosomes in angiogenesis promotion ( Skog et al, 2008 ; Hong et al, 2009 ; Ahmadi and Rezaie, 2020 ), suppression of immune response ( Yu et al, 2007 ; Clayton et al, 2008 ), induction of invasive ( Luga et al, 2012 ; Guo et al, 2019 ; Jabbari et al, 2020a ) and metastatic phenotype ( Peinado et al, 2012 ), formation of pre-metastatic niche ( Costa-Silva et al, 2015 ; Colletti et al, 2020 ). Moreover, tumoral exosomes can induce drug resistance carrying miRNAs that target antiapoptotic and immune-suppressive pathways or ABC transporters, which export chemotherapeutic agents out of recipient cells ( Santos and Almeida, 2020 ).…”
Section: Exosomes: Biogenesis Release and Functionsmentioning
confidence: 99%
“…Moreover, tumoral exosomes can induce drug resistance carrying miRNAs that target antiapoptotic and immune-suppressive pathways or ABC transporters, which export chemotherapeutic agents out of recipient cells ( Santos and Almeida, 2020 ). Given their involvement in cancer progression and their presence in different biological fluids, there have been increasing efforts toward their characterization as a source of possible diagnostic and prognostic biomarkers even in pediatric oncology ( Colletti et al, 2017 , 2019 , 2020 ; Galardi et al, 2019 , 2020 ) and as a delivery tool for biomedical applications ( Rezaie et al, 2018 ; Rahbarghazi et al, 2019 ; Jabbari et al, 2020b ; Wu Z. et al, 2020 ).…”
Section: Exosomes: Biogenesis Release and Functionsmentioning
confidence: 99%
“…Furthermore, exosomal miR-92a-3p derived from highly metastatic cancer cells promotes the epithelial-mesenchymal transition and the metastasis of low-metastatic cancer cells by regulating the PTEN/Akt pathway in hepatocellular carcinoma ( Yang B. et al, 2020 ). Moreover, neuroblastoma-secreted EVs carrying miR-375 promote osteogenic differentiation of bone marrow mesenchymal stromal cells ( Colletti et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%